Sosialisasi Pentingya Kuliah Pada Siswa SMA Negeri 5 Kota Ternate - Linda Kurnia Mustafa; Muliadi Muliadi; Nurfatimah Sugrah; Dira Ayu Annisa (Jurnal Abdimas Indonesia, 2025)
The declining interest of students in pursuing higher education has become a growing concern for universities across Indonesia. In particular, the Chemistry Education program is facing a significant challenge, as fewer students are choosing this field of study a trend that may eventually affect both the quantity and quality of future chemistry teachers. To address this issue, an outreach activity was conducted at SMA Negeri 5 Ternate City, aiming to inspire and motivate students to continue their education at the university level, especially in the field of chemistry. The program included interactive discussions and motivational mentoring sessions designed to engage students more deeply with the idea of higher learning. The evaluation results showed a positive shift in students’ perceptions of the value of higher education, along with an increased interest in the Chemistry Education program. Further analysis revealed that one major reason behind the low enthusiasm for university study is the limited access to information and guidance provided by higher education institutions. Therefore, this activity is expected to serve as an important and strategic first step in addressing the challenge of declining student interest in pursuing higher education.